2020
DOI: 10.1002/mp.13997
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of navigated endoscopy for the placement of high dose rate brachytherapy applicators in the esophagus and lung

Abstract: Purpose To evaluate the electromagnetic (EM) tracking of endoscopes and applicators as a method of positioning a high dose rate (HDR) luminal applicator. Method An anatomical phantom consisting of a rigid trachea and flexible esophagus was used to compare applicator placement measurements using EM tracking vs the traditional method using two‐dimensional (2D) fluoroscopy and surface skin markers. The phantom included a tumor in the esophagus and several pairs of optically visible points inside the lumen that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The first is the instrumentation, where a common challenge is accurate spatial co-registration, especially between planar (surface) and volumetric images or between en-face (eg, fluorescence) and crosssectional (eg, OCT) views. Co-registration between preoperative radiological and intra-operative optical techniques is enabled by EM tracking or laser-based triangulation of the intraoperative device [125,126]. Independent of the instrumentation, exogenous contrast can be used either as two different single-modality agents or combined into a single dual-modality agent such as conjugates of a gamma-emitting radionuclide and a fluorophore [123].…”
Section: Hybrid Approachesmentioning
confidence: 99%
“…The first is the instrumentation, where a common challenge is accurate spatial co-registration, especially between planar (surface) and volumetric images or between en-face (eg, fluorescence) and crosssectional (eg, OCT) views. Co-registration between preoperative radiological and intra-operative optical techniques is enabled by EM tracking or laser-based triangulation of the intraoperative device [125,126]. Independent of the instrumentation, exogenous contrast can be used either as two different single-modality agents or combined into a single dual-modality agent such as conjugates of a gamma-emitting radionuclide and a fluorophore [123].…”
Section: Hybrid Approachesmentioning
confidence: 99%
“…Computed tomography (CT) guidance is mainly used for seed implantation into cancers located at head and neck, thoracic, primary/metastatic liver/adrenal, recurrent/metastatic pelvic cavity, and spinal areas [ 29 , 33 , 43 ]. Recent testing of electromagnetic tracking of endoscopes and BT applicators indicated higher precision of HDR-BT positioning in cases with complex insertions [ 53 ]. MRI guidance is less accessible in the clinic than ultrasound and/or CT guidance, although is regularly used during pre-BT assessments [ 54 ].…”
Section: Sabt Concept and Designmentioning
confidence: 99%
“…High dose optimization and conformity of ablative BT allow achieving advanced curative effects. For instance, HDR-BT was shown effective in early-stage intra-tracheal [ 53 ] and cervical cancers [ 57 ], while LDR-BT is successfully used in prostate cancers [ 58 ]. Recent retrospective analysis indicated that HDR-BT patients had a lower incidence of acute genitourinary toxicities (grade ≥ 2) [ 59 ].…”
Section: Sabt Concept and Designmentioning
confidence: 99%
“…[7] Magnetic tracking systems have been researched by several authors [8][9][10][11][12][13][14][15][16][17] and proposed for multiple surgical operations. [18][19][20][21][22][23][24][25] A magnetic tracking system can provide effective assistance to surgeons or interventional radiologists during procedures performed in a clinical environment. [26] These systems are used to track or localize the position of instruments relative to the patient anatomy.…”
Section: Introductionmentioning
confidence: 99%